Qualitative Analysis of the Identity Resources of Hawrami People - E. Fayaz; E. Nercisyans; A. Naderi; N. Babasafari (Taḥqīqāt-i Farhangī-i Īrān, 2019)
The ethno-cultural region of Hawraman encounters a multiple and complex combination of identity sources which its understanding calls for deep and contextual investigation. Applying a qualitative approach, the present study attempts to discuss the identity sources of Hawrami people. To these end, a half-structured interview was conducted with 33 Hawrami key commentaries and experts selected with maximum variation; Data were gathered. In order to analyze the data, we used Nvivo and MAXQDA software based on conventional qualitative content analysis proposed by Lundman and Greneheim. The findings of the study demonstrated that the identity sources of Hawraman consists of four themes: “Hawrami-Kurdish ethnical identity”, “Iranian national identity”, “religious identity”, and “modern identity”. The category of Hawrami-Kurdish identity includes Hawrami language and literature, Hawrami symbols, sense of attachment and feeling proud of being a Hawrami, preserving and defending Hawrami sources and interests, music and songs and the emphasis on social integrity of different regions as Kurd people. The Iranian national identity includes the everyday presence of Persian language, music and songs, rituals and Iranian values, and national loyalty. Religious identity embraces the beliefs, rituals, Sufism, Ghaderi and Naghshbandi mysticisms, the state of religion, tolerance and revitalization-fundamentalism. In the category of modern identity, we shall see challenging the ancestor’s beliefs, intellect, criticism and awareness, humanism and tendency towards modernism, cosmopolitanism and consumption. At the end of the study, according to the findings, the identity sources of Hawrami people model was recognized and represented.